Question

Asked Aug 20, 2019

1 views

Given the partial decomposition of the rational function f(x), find A, B and C.

f(x)=(-x^(2)-12x-26)/((x+2)(x+3)(x+4))=(A)/(x+2)+(B)/(x+3)+(C)/(x+4)

Step 1

The constant value in partial decomposition of the ratio...

Tagged in

Find answers to questions asked by student like you

Show more Q&A

Q: Solve the polynomial inequality and graph the solution set on a real number line. Express the soluti...

A: Calculation:The given quadratic inequality is (x–6)(x+4)≤ 0.Change the inequality sign by equal sign...

Q: 11) In 2006 the average yearly tuition of a private college was $30,000, and it is projected to incr...

A: Let x represents the number of years after 2006 and $ y represents the yearly tuition fees, When x=...

Q: Solve the system. If there is no solution or if there are infinitely many solutions and the system's...

A: Consider the given system of equations:

Q: is a zero of f(x)=28x +88x-37x-7 2 7 3 Solve the equation 28x +88x-37x-7=0 given that (Use a comma t...

A: Since x=-7/2is a zero of the equation. We can divide the equation by x=-7/2 to get the quadratic equ...

Q: Suppose that the amount of time it takes to build a highway varies directly with the length of the h...

A: Time (T) is proportional to the length of the highway (L) and inversely proportional to the number o...

Q: Use the graph of y - f(x) to graph the function g(x)=f(x)-2 Choose the correct graph of g below y fx...

A: Click to see the answer

Q: Given the function f(x) = vx-7, (a) Find f (x) (b) Graph f and f (c) Use interval notation to give t...

A: We first replace f(x) by y. Then we switch x and y and solve for y. This new y is replaced by f^-1(x...

Q: How many quarts of pure antifreeze must be added to 7 quarts of 40% antifreeze solution to obtain a ...

A: Let us add x quarts of pure antifreeze to the 7 quarts of 40% antifreeze, to achieve 50% antifreeze ...

Q: (X) 16 (D) 16 (E) 256 26. The sequence A is defined by A 100 terms in sequence A? A +2 for each inte...

A: Given, A_1=45 and An=A_(n-1)+2. Using n=2,3,4,.. in this expression we get: A_2=47,A_3=49,A_4=51,......